Compulsive checking behavior of quinpirole-sensitized rats as an animal model of Obsessive-Compulsive Disorder(OCD): form and control - Szechtman, Henry (BioMed Central, 2001)
BACKGROUND: A previous report showed that the open field behavior of rats sensitized to the dopamine agonist quinpirole satisfies 5 performance criteria for compulsive checking behavior. In an effort to extend the parallel between the drug-induced phenomenon and human obsessive-compulsive disorder (OCD), the present study investigated whether the checking behavior of quinpirole rats is subject to interruption, which is an attribute characteristic of OCD compulsions. For this purpose, the rat's home-cage was placed into the open field at the beginning or the middle of a 2-hr test. RESULTS: Introduction of the home-cage reduced checking behavior, as rats stayed inside the cage. After 40 min, checking resurfaced, as quinpirole rats exited the home-cage often. An unfamiliar cage had no such effects on quinpirole rats or saline controls. CONCLUSIONS: Checking behavior induced by quinpirole is not irrepressible but can be suspended. Results strengthen the quinpirole preparation as an animal model of OCD compulsive checking.